Immunoinformatics based designing of a multi-epitope cancer vaccine targeting programmed cell death ligand 1 - Syed Sahajada Mahafujul Alam; Showkat Ahmad Mir; Arijit Samanta; Binata Nayak; Safdar Ali; Mehboob Hoque (Scientific Reports)
Abstract Tumor cells express programmed cell death ligand 1 (PD-L1), which recognizes the immune checkpoint molecule programmed cell death 1 (PD-1) on T cells, suppressing the antitumor immune response. Inhibiting the PD-1:PD-L1 interaction has the potential to reactivate the immune response against tumors. Recent advancements in cancer therapy have demonstrated remarkable promise of immunotherapy, which exploits immune checkpoint inhibition by small molecules or monoclonal antibodies. This strategy has shown impressive clinical success in treating a wide range of cancer subtypes, albeit with certain limitations. This study aims to design a novel multi-epitope vaccine against PD-L1 by using an immunoinformatics approach. For attaining enhanced efficacy and minimize side effects, the vaccine was constructed using antigenic, non-allergenic, and non-toxic epitopes (5 CTL, 3 HTL, and 2 B-cell epitopes) predicted from the IgV domain of PD-L1. The vaccine design includes a large ribosomal subunit protein bL12 adjuvant, a 6xHis tag for purification, and appropriate linkers to connect the epitopes. The modelled 3D structure of the vaccine construct was docked with TLR4 immune receptor, demonstrating strong antigenic properties and stable binding, as validated by molecular dynamics simulations. Immune simulation studies suggest that the vaccine construct could potentially elicit significant immune regulators such as B cells, T-cells, and memory cells. Thus, the findings indicate that the vaccine may effectively suppress the PD-1:PD-L1 axis by targeting PD-L1, restoring the anticancer immune response. However, its efficacy needs to be validated in both in vitro and in vivo settings.